2016
DOI: 10.1159/000447860
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Oil-Based Lipid Emulsion Increases Intestinal Permeability of Lipopolysaccharide in Caco-2 Cells by Downregulation of P-Glycoprotein via ERK-FOXO 3a Pathway

Abstract: Background and Aims: Elevated intestinal permeability of lipopolysaccharide (LPS) is a major complication for patients with parenteral nutrition (PN), but the pathogenesis is poorly understood. Intestinal P-glycoprotein (P-gp) is one of the efflux transporters that contribute to restricting the permeability of lipopolysaccharide via transcellular route. P-gp expression may be regulated by PN ingredients, and thus this study sought to investigate the effect of PN on the expression of P-gp and to elucidate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…P-gp, one of the most extensively studied and important drug transporters [23], has been investigated in clinical studies. In addition, elevated expression and activity of P-gp have been reported to be associated with poor clinical outcomes among cancer patients [24]. Based on these findings, a rationale was formulated for modulation of P-gp activity as a therapeutic approach [25].…”
Section: Discussionmentioning
confidence: 99%
“…P-gp, one of the most extensively studied and important drug transporters [23], has been investigated in clinical studies. In addition, elevated expression and activity of P-gp have been reported to be associated with poor clinical outcomes among cancer patients [24]. Based on these findings, a rationale was formulated for modulation of P-gp activity as a therapeutic approach [25].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to further understand the underlying mechanism, we examined possible signalling pathways that may mediate the regulation of P-gp upon DEX treatment, including ERK, PI3K/Akt, JNK, p38 and AMPK. These pathways were examined because: i) Previous studies demonstrated that DEX may elicit various non-anesthetic effects via these pathways ( 17 , 30 ) and ii) these pathways have been reported to be involved in the regulation of P-gp expression in response to a variety of extracellular stimuli ( 31 , 32 ). In the present study, though it lacks statistical significance, it seems that the intracellular accumulation of Rhodamine 123 in L02 cells was slightly increased by inhibition of the ERK and PI3K/Akt pathways, suggesting that these pathways may contribute to the activation of P-gp expression under normal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…TEER was measured with an epithelial voltmeter under open-circuit conditions (WPI, Sarasota, FL) as described previously. 27…”
Section: Evaluation Of Intestinal Barrier Function In Vitromentioning
confidence: 99%